Extensively drug-resistant acinetobacter baumannii meningitis which successfully treated with tigecycline; a case report of preterm newborn (Annals of Medical Research, 2021)
Acinetobacter baumannii (A. baumannii) meningitis is a state difficult to treat with a high mortality rate, since antibiotics have low CSF penetration level and antibiotic resistance is frequently encountered. Multidrug-resistance is common in hospital-acquired A. baumannii infections, and in these cases, colistin treatment is frequently used as the last option. Colistin-resistant A. baumannii infections are reported in recent years. We present a case of preterm newborn who developed extensively drug-resistant (carbapenem and colistin resistance) A. baumannii meningitis after ventriculoperitoneal shunt operation. Although not approved in children, combined intravenous treatment including tigecycline, meropenem and colistin provides clinical and bacteriological recovery in colistin and carbapenem-resistant A. baumannii meningitis.
Keywords: Acinetobacter; colistin; meningitis; tigecycline